Cancer cells resist antibody-mediated destruction by neutrophils through activation of the exocyst complex. Issue 6 (21st June 2022) - van Rees, Dieke J; Bouti, Panagiota; Klein, Bart; Verkuijlen, Paul J H; van Houdt, Michel; Schornagel, Karin; Tool, Anton T J; Venet, David; Sotiriou, Christos; El-Abed, Sarra; Izquierdo, Miguel; Guillaume, Sébastien; et al.
Abstract : Background: Neutrophils kill antibody-opsonized tumor cells using trogocytosis, a unique mechanism of destruction of the target plasma. This previously unknown cytotoxic process of neutrophils is dependent on antibody opsonization, Fcγ receptors and CD11b/CD18 integrins. Here, we demonstrate that tumor cells can escape neutrophil-mediated cytotoxicity by calcium (Ca 2+ )-dependent and exocyst complex-dependent plasma membrane repair. Methods: We knocked down EXOC7 or EXOC4, two exocyst components, to evaluate their involvement in tumor cell membrane repair after neutrophil-induced trogocytosis. We used live cell microscopy and flow cytometry for visualization of the host and tumor cell interaction and tumor cell membrane repair. Last, we reported the mRNA levels of exocyst in breast cancer tumors in correlation to the response in trastuzumab-treated patients. Results: We found that tumor cells can evade neutrophil antibody-dependent cellular cytotoxicity (ADCC) by Ca 2+ -dependent cell membrane repair, a process induced upon neutrophil trogocytosis. Absence of exocyst components EXOC7 or EXOC4 rendered tumor cells vulnerable to neutrophil-mediated ADCC (but not natural killer cell-mediated killing), while neutrophil trogocytosis remained unaltered. Finally, mRNA levels of exocyst components in trastuzumab-treated patients were inversely correlated to complete response to therapy. Conclusions: Our results support that neutrophil attack towards antibody-opsonized cancer cells by trogocytosis induces an active repair process by the exocyst complex in vitro. Our findings provide insight to the possible contribution of neutrophils in current antibody therapies and the tolerance mechanism of tumor cells and support further studies for potential use of the exocyst components as clinical biomarkers.